2010
DOI: 10.1007/s13317-010-0008-2
|View full text |Cite
|
Sign up to set email alerts
|

Role of regulatory T cells in rheumatoid arthritis: facts and hypothesis

Abstract: Regulatory T cells (Treg) are a CD4 + lymphocyte subset involved in self-tolerance and autoimmunity prevention. There is evidence for a phenotypic and/or functional impairment of this cell subset during the natural history of several chronic autoimmune/inflammatory diseases, including rheumatoid arthritis (RA). Although the intracellular transcription factor FoxP3 is thought to be the master regulator of Treg cell function, a number of other molecules expressed on the cell surface have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 55 publications
0
11
0
1
Order By: Relevance
“…The imbalance of the proportion of effector cells and regulatory cells caused by the loss of autoimmune tolerance plays an important role in the pathogenesis of RA [67,68]. Studies have shown that SM-MSCs may be involved in the regulation of immune homeostasis in healthy joints, and the failure of this immune regulation is the basis of the development of RA.…”
Section: Study Of Sm-mscs In Rheumatoid Arthritis (Ra)mentioning
confidence: 99%
“…The imbalance of the proportion of effector cells and regulatory cells caused by the loss of autoimmune tolerance plays an important role in the pathogenesis of RA [67,68]. Studies have shown that SM-MSCs may be involved in the regulation of immune homeostasis in healthy joints, and the failure of this immune regulation is the basis of the development of RA.…”
Section: Study Of Sm-mscs In Rheumatoid Arthritis (Ra)mentioning
confidence: 99%
“…Animal models of the disease, although important for our understanding of the multiple mechanisms involved, must be integrated with more in depth studies into the human pathology. This would throw light on the etiopathogenetic aspects that require further explanation and would provide further elements to promote the therapeutic use of T REG cells in the treatment of systemic auto-immune pathologies (24).…”
Section: Gitrmentioning
confidence: 99%
“…The mechanisms responsible for the induction of autoimmunity are poorly understood. Several articles published in this, as well as previous issues of the journal, are focusing on the investigation of mechanisms inducing autoimmunity and indeed autoimmune disease [ 18 , 69 83 ]. The mechanism of molecular mimicry and immunological cross-reactivity between infectious agents or xenobiotics and disease-specific autoantigens has been used to explain the loss of immunological tolerance in autoimmune gastrointestinal and liver diseases, including PBC [ 84 100 ].…”
Section: Primary Biliary Cirrhosismentioning
confidence: 99%
“…As well, studies on genetically similar populations living under different conditions have demonstrated different incidence rates of autoimmune disease. The induction of autoimmune disease by these exposures may be through various mechanisms such as the alteration of autoantigen structure, altered expression of antigens, stimulatory effects on the immune system, T-cell dysregulation, apoptosis-mediated autoimmunity, molecular mimicry and immunological cross-reactivity [ 5 , 14 18 ].…”
Section: Introductionmentioning
confidence: 99%